HISTORY OF ARCHEOLOGICAL DISCOVERIES RELATED TO THE FIRST URBAN CULTURE OF THE FERGANA VALLEY - Khakimov, Abdumuxtor Abduxalimovich; Ogli Komilov, Ubaydullo Ibrokhimjon (Current Research Journal of History, 2021)
The article describes the emergence and development stages of the first cities in the Fergana Valley. Also, the history of archeological discoveries related to the first urban culture of the Fergana Valley is analyzed, taking into account that the scientific study and analysis of these issues can be carried out only due to archaeological research.